Characterization Of Carbohydrate And Protein Accumulation In Oil Palm Trees - Natra, Joseph Stalin (2018)
This study characterized the accumulation of non-structural carbohydrate and protein in the oil palm trees. The starch and sugar are the main constituent contained in non-structural-carbohydrate. In this research, the starch and sugar accumulation in standing oil palm trees are characterized based on different growth conditions, then further analysed based position along the oil palm stem and influence of the weather fluctuation. The effect of storing on non-structural carbohydrate and protein content based on height in felled oil palm trunk also has been characterized. In the study on standing oil palm trees, eight oil palm trees was selected and divided equally into two different groups which are Non-Fruit Removal Trees (NFRT) and Fruit Removal Trees (FRT).